2014
DOI: 10.1093/eurheartj/ehu214
|View full text |Cite
|
Sign up to set email alerts
|

Bivalirudin is superior to heparins alone with bailout GP IIb/IIIa inhibitors in patients with ST-segment elevation myocardial infarction transported emergently for primary percutaneous coronary intervention: a pre-specified analysis from the EUROMAX trial

Abstract: AimsIn the HORIZONS trial, in-hospital treatment with bivalirudin reduced bleeding and mortality in primary percutaneous coronary intervention (PCI) compared with heparin and routine glycoprotein IIb/IIIa inhibitors (GPI). It is unknown whether this advantage of bivalirudin is observed in comparison with heparins only with GPI used as bailout.Methods and resultsIn the EUROMAX study, 2198 patients with ST-segment elevation myocardial infarction (STEMI) were randomized during transport for primary PCI to bivalir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 17 publications
3
78
0
3
Order By: Relevance
“…40 Similarly, anticoagulant choice is an important determinant of access and non-access site major bleeding complications. Changes in anticoagulant practice from heparin and glycoprotein IIb/IIIa regimes to bivalirudin have been demonstrated to be associated with reductions in major bleeding and mortality, 41,42 with a recent analysis of the National Cardiovascular Data Registry (NCDR) data set, suggesting that changes in anticoagulation strategies over time contributed to ≈50% of the annual reduction in bleeding observed in acute coronary syndrome and elective PCI 43 with more aggressive anticoagulant regimes associated with significant increases in bleeding complications observed in many of the studies included in this meta-analysis (Table IX in the Data Supplement).…”
Section: Discussionmentioning
confidence: 99%
“…40 Similarly, anticoagulant choice is an important determinant of access and non-access site major bleeding complications. Changes in anticoagulant practice from heparin and glycoprotein IIb/IIIa regimes to bivalirudin have been demonstrated to be associated with reductions in major bleeding and mortality, 41,42 with a recent analysis of the National Cardiovascular Data Registry (NCDR) data set, suggesting that changes in anticoagulation strategies over time contributed to ≈50% of the annual reduction in bleeding observed in acute coronary syndrome and elective PCI 43 with more aggressive anticoagulant regimes associated with significant increases in bleeding complications observed in many of the studies included in this meta-analysis (Table IX in the Data Supplement).…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22] In HORIZONS-AMI, EUROMAX, BRIGHT and MATRIX, bivalirudin was generally superior to unfractionated heparin in terms of reduced bleeding but was associated with higher rates of acute stent thrombosis in 3 out of the 4 studies. All studies used higher rates of GPI in the comparator heparin arm and some continued the bivalirudin infusion post-PPCI.…”
Section: Ppci: Procedural Considerationsmentioning
confidence: 99%
“…A recent prespecified analysis from EUROMAX demonstrated that bleeding reductions with bivalirudin were observed even in the setting of low-dose heparin without GPI. 10 In the current prespecified analysis from EUROMAX, we investigated whether the selection of arterial access site had an impact on 30-day outcomes and whether radial access mitigated the bleeding reduction benefit of bivalirudin.…”
Section: Outcomes With Revasulariation and Stents In Acute Myocardialmentioning
confidence: 99%